Climate-friendly food-choice intentions among emerging adults: extending the theory of planned behavior with objective ambivalence, climate-change worry and optimism - Jylhä, Kirsti M.; Ojala, Maria; Odisho, Sandy; Riise, Anja (Frontiers in Psychology, 2023)
Climate-friendly food choices are still relatively rarely addressed in studies investigating climate engagement, particularly among young people. To address this research gap, we conducted a questionnaire study with senior high school students (N = 474). Our overarching theoretical framework is the Theory of Planned Behavior (TPB), which we extended with emotional factors (climate-change worry and optimism) and attitudinal ambivalence. We found that all factors included, except for optimism, correlated with the food-choice intentions. In multiple regression analyses, worry was the second strongest predictor, after attitudes. Moreover, a measure of objective ambivalence moderated the correlation between attitudes and intentions by weakening it. The results support the validity of using the TPB model when explaining intentions to make climate-friendly food choices among emerging adults. However, our results suggest that it is also important to consider emotions—in this case climate-change worry—and the existence of conflicting evaluations about choosing climate-friendly food.